2015
DOI: 10.4315/0362-028x.jfp-15-150
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Antimicrobial Resistance Prof ile of Methicillin-Resistant Staphylococcus aureus in Retail Chicken

Abstract: The emergence of livestock-associated methicillin-resistant Staphylococcus aureus (MRSA) in food-producing animals is of increasing interest, raising questions about the presence of MRSA in food of animal origin and potential sources of transmission to humans via the food chain. In this study, the prevalence, molecular characterization, virulence factors, and antimicrobial susceptibility patterns of MRSA isolates from 200 retail raw chicken samples in Egypt were determined. MRSA was detected by positive amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 28 publications
6
33
0
Order By: Relevance
“…Consequently, the resistance levels found in this study can be explained by the indiscriminate use of antimicrobials in humans treating diseases, which is a worrying trend. Similar antibiotic resistance pattern of the S. aureus strains isolated from different types of sweet, candy, and ready to eat food samples have also been reported from Brazil (Kroning et al, ), Iran (Dehkordi et al, ), Italy (Paludi et al, ), Egypt (Sallam, Abd‐Elghany, Elhadidy, & Tamura, ), USA (Jackson, Davis, & Barrett, ), and Nigeria (Fowoyo & Ogunbanwo, ). Fowoyo and Ogunbanwo () reported that the S. aureus strains isolated from ready to eat foodstuffs exhibited the high prevalence of resistance against ampicillin (86.70%), trimethoprim–sulfamethoxazole (74.90%), amoxicillin–clavulanic acid (52.50%), cefotaxime (3.50%), oxacillin (35.70%), ciprofloxacin (23.90%), erythromycin (15.70%), gentamicin (11.40%), and ofloxacin (7.10%).…”
Section: Resultssupporting
confidence: 72%
“…Consequently, the resistance levels found in this study can be explained by the indiscriminate use of antimicrobials in humans treating diseases, which is a worrying trend. Similar antibiotic resistance pattern of the S. aureus strains isolated from different types of sweet, candy, and ready to eat food samples have also been reported from Brazil (Kroning et al, ), Iran (Dehkordi et al, ), Italy (Paludi et al, ), Egypt (Sallam, Abd‐Elghany, Elhadidy, & Tamura, ), USA (Jackson, Davis, & Barrett, ), and Nigeria (Fowoyo & Ogunbanwo, ). Fowoyo and Ogunbanwo () reported that the S. aureus strains isolated from ready to eat foodstuffs exhibited the high prevalence of resistance against ampicillin (86.70%), trimethoprim–sulfamethoxazole (74.90%), amoxicillin–clavulanic acid (52.50%), cefotaxime (3.50%), oxacillin (35.70%), ciprofloxacin (23.90%), erythromycin (15.70%), gentamicin (11.40%), and ofloxacin (7.10%).…”
Section: Resultssupporting
confidence: 72%
“…Virtually all of the isolates used in this study originated from countries in the aforementioned regions. In particular, all mecA -positive isolates were of Egyptian origin, where a high contamination rate with MRSA has been reported for retail chicken meat, possibly due to insufficient hygiene during handling as well as ample use of antimicrobial agents [29]. Notably, many of our samples appeared to be home-made, where adherence to hygienic standards during slaughter and handling is likely to be inferior when compared to commercially produced meat.…”
Section: Discussionmentioning
confidence: 90%
“…Pcr assay: PCR assay was performed for the detection of the nuc (encoding for the S. aureus-specific thermonuclease) gene and coa gene encoding for coagulase as previously described by Sallam et al (2015) and Himabindu et al (2009), respectively. The primers sequences (Hokkaido System Science Co.Ltd., Hokkaido, Sapporo, Japan and Metabion, Germany) and its amplicons size are listed in Table 1 12.5 µl master mix (Thermo scientific, USA); 1 µl of each primer; 2 µl DNA template and volume of the reaction mixture was completed to 25 µl using DNase/RNase-free water.…”
Section: Phenotypic Antimicrobial Susceptibility Testingmentioning
confidence: 99%